The relationship between perceived organizational support and insomnia in Chinese nurses: The Serial multiple mediation analysis - Wang, Mei-Fang; He, Qing; Liu, Zhuo; Du, Juan (Frontiers in Psychology, 2022)
Background: Nurses are in high-pressure, high-load and high-risk environment for a long time, and their insomnia cannot be ignored. Insomnia not only has a negative impact on the physical and mental health of nurses, but also on the efficiency and quality of nursing work. Objective: The purpose of this study was to investigate the multiple mediating effect of psychological capital, effort-reward ratio and overcommitment in the relationship between perceived organizational support and insomnia among Chinese nurses. Methods: A cross-sectional study has been carried out in a tertiary grade A hospital in Shandong Province, China from March 2021 to May 2021. The demographic questionnaire, Perceived Organization Support Questionnaire, Psychological Capital Questionnaire, Chinese version Effort-Reward Imbalance and Athens Insomnia Scale were used for data collection. SPSS PROCESS 3.4 macro program developed by Hayes was used to test the serial multiple mediation. Effective respondents were 658 (81.2%). Descriptive analysis, independent-samples t-test, one-way analysis of variance, Pearson correlation analyses, ordinary least-squares regression and the bootstrap method were used for data analysis. Results:Nurses' perceived organizational support was positively correlated with psychological capital, and was significantly negatively correlated with effort-reward ratio, overcommitment , and insomnia ; Psychological capital was negatively correlated with effort-reward ratio , overcommitment and insomnia , respectively; effort-reward ratio and overcommitment were significantly positively correlated with insomnia (all P < 0.001), respectively. Overall, the serial-multiple mediations of psychological capital and effort reward ratio, overcommitment in the relationship between perceived organizational support and insomnia were found to be statistically significant. In the model of perceived organizational support - psychological capital - effort-reward ratio - insomnia, the overall mediating effect was -0.080 (95%CI: -0.109 -0.058)；In the model of perceived organizational support - psychological capital - overcommitment - insomnia, the overall mediating effect was -0.085 (95%CI: -0.109 -0.064). Conclusions: Perceived organizational support had direct negative influence on insomnia. Psychological capital and effort-reward ratio/overcommitment acted as chained mediating factor could partially relieve insomnia symptoms related to perceived organizational support. Supportive working environment should be provided, and improving psychological capital levels, and declining effort-reward ratio/overcommitment to help nurses coping with insomnia symptoms.